Role of Uric Acid as a Prognostic Factor in Acute Myocardial Infacrtion - Chowdhury, Md Zahangir Alam; Sarwar, Mirza Golam; Jalil, Md Abdul (Journal of Chittagong Medical College Teachers’ Association, 2017)
Uric acid has been proven to be a negative prognostic indicator in patients with acute myocardial infarction and heart failure. So the aim of the present study is to evaluate the uric acid as a predictor of outcome after acute myocardial infarction. A total of 120 patients presenting with acute myocardial infarction were included in the study where case were the AMI with heart failure and arrhythmia and control were the only Ami patients. Patients were evaluated in relation with clinical features, risk factors, complications, heart failure with Killip Class and serum uric acid level. Sociodemographic profiles of the study populations were matched in case and control group. Regarding different biochemical variables of case and control where serum uric acid was found significantly higher among the case group than the control (p<0.05). Among different risk factors of MI where hypertension, smocking, DM and sedentary lifestyle were found common in both case and control group showing the different signs of the case and control where all were more or less common among both groups. Serum uric acid level and arrhythmia class among the case group. Regarding prognostic evaluation of uric acid after MI where complete recovery, arrhythmia, recurrent MI, hospital stay and death was significantly found associated with risk stratification. Serum uric levels are raised during an episode of myocardial infarction and more so when the patient is in heart failure. There is a positive correlation between rising serum uric acid levels with higher Killip Class at the time of admission. Thus uric acid can be used as a prognostic indicator in patients presenting with myocardial infarction more so if they are in heart failure. JCMCTA 2016 ; 27 (2) : 63- 66